Coclustering of ErbB1 and ErbB2 Revealed by FRET-Sensitized Acceptor Bleaching - Szabó, Ágnes (The Biophysical Society, 2010)
Classical theory states that ligand binding induces the dimerization of ErbB proteins, leading to their activation. Although we and other investigators have shown the existence of preformed homoclusters of ErbB receptors and analyzed their composition, the stoichiometry of their heteroclusters has not been quantitatively described. Here, we report the development of the fluorescence resonance energy transfer (FRET)-sensitized acceptor bleaching (FSAB) technique to quantitate the ratio of ErbB1 and ErbB2 in their heteroclusters. In FSAB, photolabile acceptors within FRET distance from photostable donors are excited and photobleached by FRET, and the fraction of acceptors that are participating in FRET is determined. In quiescent SKBR-3 breast cancer cells, ∼35% of ErbB1 and ∼10% of ErbB2 have been found in heteroclusters. Epidermal growth factor (ligand of ErbB1) increased the fraction of ErbB2 heteroclustering with ErbB1, whereas the ratio of heteroclustered ErbB1 did not change significantly. The fractions of heteroclustered ErbB1 and ErbB2 were independent of their expression levels, indicating that the formation of these clusters is not driven by the law of mass action. In contrast, the FRET efficiency depended on the donor/acceptor ratio as expected. We present a model in which preformed receptor clusters are rearranged upon ligand stimulation, and report that the composition of these clusters can be quantitatively described by the FSAB technique.